Implementation of Chatgpt As A Learning Supervision Assistant In Analyzing Rpp And LKPD In Middle Schools - Celine Yinnie; Dety Mulyanti (Journal of Innovative and Creativity, 2025)
This study aims to analyze the application of ChatGPT as a learning supervision assistant in the evaluation process of Lesson Plans (RPP) and Student Worksheets (LKPD) in secondary schools. The background of the study stems from the need to improve the effectiveness of academic supervision, which has faced various obstacles such as time constraints, teacher administrative burdens, and inconsistencies in the quality of learning document reviews. Large Language Model (LLM)-based artificial intelligence technology such as ChatGPT offers new opportunities in simplifying the supervision process, increasing analysis accuracy, and accelerating the improvement of learning documents. This study uses a descriptive qualitative approach with documentation study methods, observation, and interactive analysis. The research instruments consisted of observation sheets on the quality of RPP and LKPD, analysis guidelines based on the Minister of Education and Culture Regulation, and the results of interactions using ChatGPT as a supervision tool. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that ChatGPT is able to provide in-depth analysis of RPP and LKPD components, including the suitability of learning outcomes, clarity of learning steps, assessment quality, and the appropriateness of teaching materials. Furthermore, the use of ChatGPT helps teachers identify document weaknesses, provide alternative improvements, and expedite the supervision process without compromising the quality of the analysis. The research discussion confirms that the use of ChatGPT is relevant to the demands of digital transformation in education, particularly in improving teacher professionalism and the effectiveness of academic supervision. The study's conclusion confirms that ChatGPT is a significant innovation in supporting learning supervision in secondary schools, but still requires professional guidance to maintain validity and pedagogical context.